Efficient Degradation of Congo Red Under Ultrasonic Irradiation Using Carbon Quantum Dots /Cellulose Composites - Pang Yean Ling; Soh Christopher Chun Min; Lim Steven (E3S Web of Conferences)
In this study, carbon quantum dots (CQDs) and composites at various concentrations were successfully synthesized via a facile hydrothermal method. The structure and morphology of the CQDs/composites were characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), thermal analysis, and surface area analysis. The sonocatalytic activities of the CQDs/composites were investigated in an ultrasonic bath to study the degradation of Congo Red. The effects of various parameters, including the oxidant dosage, initial Congo Red concentration and solution pH on the sonocatalytic degradation of Congo Red were examined to optimize the sonocatalytic performance. The optimum condition for degrading 10 mg/L of Congo Red was found to be in the presence of 1.5 g/L of CQD/Cell-0.5, 0.75 mM of sodium persulfate and a solution pH of 3, to achieve a degradation efficiency of 75.0% at ultrasonic frequency of 25 kHz and power of 200 W. Thus, CQD/Cellulose is a promising green, non-metal sonocatalyst for textile wastewater treatment.